2022
DOI: 10.1177/00033197221091605
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid to Albumin Ratio Can Predict Contrast-Induced Nephropathy in ST-Elevation Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Intervention

Abstract: Contrast-induced nephropathy (CIN) is one of the common complication of ST-elevation myocardial infarction (STEMI) following primary percutaneous coronary intervention (pPCI). Serum uric acid to albumin ratio (UAR) is a novel marker, which is associated with acute kidney injury in intensive care unit patients. We investigated the predictive value of UAR for the development of CIN in STEMI patients (n = 1379) after pPCI. The diagnosis of CIN was made based on an increase of basal creatinine levels >.5 mg/dL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 48 publications
2
22
0
1
Order By: Relevance
“… 15 Recently, Faysal et al also demonstrated that sUAR (>1.62) had a greater predictive value for contrast-induced nephropathy, and was superior to serum uric acid and albumin. 17 In our study, we found that sUAR had a moderate predictive value for PC-AKI after PCI in patients with STEMI, and it was also superior to serum uric acid and albumin. However, when the definition of PC-AKI was consistent with that described by Faysal et al, our result showed that the AUC of sUAR for predicting PC-AKI was not a good predictive value (AUC=0.548).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“… 15 Recently, Faysal et al also demonstrated that sUAR (>1.62) had a greater predictive value for contrast-induced nephropathy, and was superior to serum uric acid and albumin. 17 In our study, we found that sUAR had a moderate predictive value for PC-AKI after PCI in patients with STEMI, and it was also superior to serum uric acid and albumin. However, when the definition of PC-AKI was consistent with that described by Faysal et al, our result showed that the AUC of sUAR for predicting PC-AKI was not a good predictive value (AUC=0.548).…”
Section: Discussionsupporting
confidence: 48%
“… 15 , 16 Recently, Faysal et al conducted a retrospective study and found that sUAR was an independent predictor of contrast-induced nephropathy. 17 However, the sample size was relatively small and the definition of contrast-induced nephropathy was proved to be not often use in patients with STEMI. 18 , 19 Therefore, it is still uncertain whether the sUAR has predictive value for predicting PC-AKI and in-hospital major adverse clinical events (MACEs) after PCI in patients with STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…12 A recent study, found that the UAR was higher in STEMI patients who developed contrast-induced nephropathy (CIN) after pPCI, and it was an independent predictor of the development of CIN in those patients. 28 In this investigation, we observed that the UAR was an independent predictor of NR development. It was worth noting that the AUC of the UAR was greater than that of serum UA or albumin alone.…”
Section: Discussionmentioning
confidence: 58%
“…16,17 The frequency of CIN occurrence is between 6.4 and 27.7%. 18 In a study conducted with a stable angina pectoris patient group, the rate of CIN after coronary angiography was 15.7%. 7 In another study conducted with an acute coronary syndrome patient group, the rate was found to be 27.7%.…”
Section: Discussionmentioning
confidence: 99%